Cytokines Genotype-Phenotype Correlation in Nonalcoholic Steatohepatitis. (9th August 2017) - Bocsan, Ioana Corina; Milaciu, Mircea Vasile; Pop, Raluca Maria; Vesa, Stefan Cristian; Ciumarnean, Lorena; Matei, Daniela Maria; Buzoianu, Anca Dana
Abstract : NASH consists in lipid accumulation in hepatocytes that trigger oxidative stress, secretion of proinflammatory cytokines leading to steatohepatitis (NASH). The study aimed to investigate the levels of proinflammatory (TNF- α and IL-6) along with anti-inflammatory cytokine IL-10 in patients with NASH and to correlate the cytokines' level with their polymorphism. Sixty-six patients with NASH and 30 healthy volunteers were included in the study. The plasmatic level of IL-6, IL-10, and TNF- α were determined by ELISA. IL-10 -1082 G/A, IL-6 -174 G/C, and TNF- α -308 G/A polymorphisms were determined using the PCR-RFLP technique. IL-6, TNF- α, and CRP levels were significantly higher in patients with NASH. There was a positive correlation between proinflammatory cytokines and a negative correlation between IL-10 and proinflammatory markers. The G allele and GG genotype of IL-6 -174 G/C polymorphism were more frequently noticed in NASH patients. Regarding IL-10 -1082 G/A polymorphism, the AA genotype was correlated with NASH and with a low plasmatic level of IL-10. The A allele in position 308 of the TNF- α gene was associated with high level of cytokine. In conclusion, there was an imbalance between pro- and anti-inflammatory cytokines in NASH patients. IL-10 -1082 G/A and TNF- α -308 G/A genotypes were correlated with the plasmatic levels of cytokines.